Tre tipi di ipotetica o due? Considerazioni sul periodo ipotetico nella lingua italiana - Salmeri, Claudio (Neophilologica, 2011)
The Italian "periodo ipotetico" (a conditional clause or hypothetical phrase) is a structure composed of two clauses. The main one is introduced chiefly by se and it indicates the condition (or supposition) on which something else is dependent (the other clause). Many canonical grammar books assert that there are three types of hypothesis/consequence situations: real, unlikely and no longer possible. The aim of this article is to disprove this traditional thesis. With a couple of examples, it is shown that there are in fact only two types of "periodo ipotetico".